The classroom of choice : giving students what they need and getting what you want - Erwin, Jonathan C., 1954- (Association for Supervision and Curriculum Development, 2004)
"Erwin presents nearly 200 easily adaptable strategies designed to customize and manage a motivated classroom environment based on William Glasser's Choice Theory."--Electronic Library